Increasing Community Environmental Awareness through Geodiversity Conservation Activities at Ciletuh, Sukabumi, West Java - HADIAN, Mohamad Sapari; YULIWATI, Ayu Krishna; PRIBADI, Krishna Nur (Journal of Environmental Management and Tourism, 2016)
The demand for precious stone increased sharply threatens the environment sustainability. Geopark is one of the forms of sustainable development that implement new paradigm of natural resources management, which makes natural resources as a source of economic growth through tourism development. Geoheritage is geodiversity that is more valuable as an inheritance, as it became a record of an event on earth. Geological features are significant of scientific, educational, and cultural. Geological conservation is conducted on extraordinary geological phenomenon and the first step to take advantage of geodiversity which is through a planned program to protect its existence. Three main reason for geodiversity conservation, namely: has the values of science, which is beneficial for human life and ecosystems supporting, non-renewable nature, many forms of geodiversity very sensitive to disturbance, especially threatened due to various human activities. Ciletuh region have unique geological diversity and the age of the rocks are the oldest in West Java. The results showed that the level of public awareness of the environment is still low, because they tend to prioritize their livelihood, and have the tendency to exploit natural resources. Therefore, it is needed a strong environmental campaign to raise public awareness that geodiversity needs to be protected.
Keywords: environmental awareness; geological conservation